Control químico de la mortaja blanca de la papa causada por el hongo Rosellinia sp. - Guerrero G., Omar (Instituto Colombiano Agropecuario - ICA, 2019)
Two trials were carried out in order to obtain chemical control of the disease Calied "Mortaja blanca" in potato caused by the fungus Rosellinia sp. The first trial was held in PotosI (Nariño), a split plot design was used with the fungicides metiltiofanato 5 kg/ha; carbendazim 5 L/ha; carboxin + captan 2 kg/ha; thiabendazole 2 L/ha and benomyl 1 kg/ha sprayed on three combinations, at planting and ridging; plants emergence, ridging and at planting, plant emergence and ridging. The second trial was carried out PotosI (Nariño) with a randomized blocks desing, using the fungicide metiltiofanato and carbendazim in dossages of 3, 4, 5 kg/ha divided by three spray epoques, at planting, plant emergence and ridging. In the two trials were evaluated plants wilt and yield of healthy and damage tubers. The results of the first trial showed that metiltiofanato and carbendazim sprayed at planting time, plant emergence and ridging time can control the disease in 96% and 95% respectively. According to economic analysis, the best treatment was metiltiofanato. The obtained results from the second trial showed that the fungicides metiltiofanato and carbendazim with the three evaluated dossages gave and excellent protection against the disease with control percentajes between 93.2% and 95.5% without any significative difference among them with high significative differences with the check. The economic analysis showed that metiltiofanato was the best treatment using 1.5 kg/ha sprayed on the planting, emergence and ridging time respectively followed of carbendazim 1.5 L/ha sprayed in the same was before mentioned.